Fabrication of In Situ Grown Hydroxyapatite Nanoparticles Modified Porous Polyetheretherketone Matrix Composites to Promote Osteointegration and Enhance Bone Repair - Wang, Ningning; Qi, Desheng; Liu, Lu; Zhu, Yanlin; Liu, Hong; Zhu, Song (Frontiers in Bioengineering and Biotechnology, 2022)
Repairment of critical-sized bone defects is a serious problem that stimulates the development of new biomaterials. In this study, nano hydroxyapatite (nHA) doped porous polyetheretherketone (pPEEK) were successfully fabricated by the thermally induced phase separation method and hydrothermal treatment. Structural analysis was performed by X-ray diffraction (XRD). The water contact angles and scanning electron microscopy (SEM) were measured to assess physical properties of surfaces. The mechanical strength of the composites is also determined. Micro computed tomography (CT) is used to characterize nHA content of the composites. The in-vitro bioactivity of the composites with or without nHA was investigated by using murine pre-osteoblasts MC3T3-E1 and the results of cytotoxicity and cell proliferation assays revealed that the cytocompatibility of all specimens were good. Adherence assays were employed to examine the adhesion and morphology of cells on different materials. However, nHA doped composites induced cell attachment and cell spreading more significantly. Osteogenic differentiation was investigated using alkaline phosphatase (ALP) activity and alizarin red staining (ARS), and these in vitro results demonstrated that composites containing nHA particles enhanced osteoblast differentiation. Its effectiveness for promoting osteogenesis was also confirmed in an in-vivo animal experiment using a tibial defective rat model. After 8 weeks of implantation, compared to the pure PEEK and pPEEK without nHA groups, the nHA-pPEEK group showed better osteogenic activity. The results indicate that the nHA-pPEEK composites are possibly a well-designed bone substitute for critical-sized bone defects by promoting bone regeneration and osteointegration successfully.